Therapeutic management of Dermatosis in Rabbits - Thakre, B.J.; Parmar, Vijay L.; Kumar, Binod; Joseph, J.P.; Patel , J.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Psoroptic mange occurs in the ears of domestic and wild animals, particularly in the ears of rabbits. It is caused by Psoroptes cuniculi (Darzi and Samuel, 2001, Bhardwaj et al., 2012). It is a common parasitic disease problem in both pet and commercial rabbits. These ear mites do not burrow, they feed on skin tissue, which irritates the skin and causes lesions and subsequently produces the scabs which protect the mites from the environment and shield them from removal by the animal when it scratches. In India with hot and humid climate, the incidence of the skin infections especially mange in the rabbits is very high (Aulakh et al., 2003). Mange leads to listlessness, anorexia, emaciation complication of middle or inner ear, wry neck and deaths resulting in considerable economic losses (Ravindran et al., 2000). Ivermectin is used as a broad spectrum parasiticide in domestic animals and is also recommended for treatment of ear mange in rabbits. Several studies have been conducted on the dose levels and duration of parentral administration of ivermectin in rabbits affected with ear mange (Fajimi et al., 2002, Jana et al.,2004, Hansen et al.,2005, Panigrahi and Gupta, 2013). The present study was carried out to evaluate the effect of parentral administration followed by oral administration of ivermectin against Psoroptic mange in rabbits.